SPICE simulation methodology to diagnose defects in upscaled Si/ perovskite tandem solar cells - Jeon, Gamhyo; Kim, Younghyun; Lim, Jae-Gwang; Lee, Doh-Kwon; Park, Jong-Keuk; Choi, In Woo; Kim, Inho (Pergamon Press Ltd., 2025)
As the power conversion efficiency (PCE) of Si solar cells has reached its limits, there is growing interest in Si/ perovskite tandem solar cells to overcome the single junction efficiency limit. As for single-junction cells, the maximum efficiency of Si solar cells is constrained to 33 % according to the Shockley-Queisser limit. However, the theoretical limit of the PCE of double junction tandem solar cells based on a Si bottom cell is 45 %, which is 1.5 times greater than that of silicon cells, sparking an upsurge in research activity in this area. Large-area scaling is vital for the commercialization of tandem solar cells. However, the unevenly distributed electrical defects formed during this process poses a significant challenge in maintaining high efficiency on large area cells. In this study, we developed an electrical diagnosis methodology using PySPICE to simulate upscaled Si/perovskite tandem solar cells. The electrical circuits were arranged in a 2D array, constituting a two-dimensional distributed diode model, enabling the formulation of a unit cell and its subsequent scaling up to a large area. Using the simulator we developed, we investigated the influence of two kinds of typical electrical defects (open and shunt defects) on the device performances of upscaled Si/perovskite tandem solar cells (M10-size). The diagnosis methodology is expected to enable the retrospective tracing of the sources of efficiency reduction in upscaled large area tandem solar cells. The results from this study will lay the groundwork for a novel approach to analyzing the non-uniformity that arises when scaling up Si/perovskite tandem solar cells to a large area.